Pengaruh ROA dan DER pada Rasio PBV dengan VAICTM sebagai Pemoderasi - Nugraha, Made Yuvi Adriana; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 31 No 6 (2021), 2021)
The aim of this study is to analyze the effect of return on assets (ROA) and debt to equity ratio (DER) on the price to book value (PBV) ratio with the value added intellectual coefficient (VAIC TM ) as moderating variable. The population of this study is all companies that were listed on the Indonesia Stock Exchange at 2019 year end. The research sample of 138 companies was determined using simple random sampling and the number of samples was determined using the Slovin formula. The hypothesis in this study was tested using moderated regression analysis. The results of  the analysis show that ROA had a positive effect on the PBV ratio, while DER had no effect on the PBV ratio, and VAIC TM did not moderate the effect of ROA and DER on the PBV ratio. The results of this study confirm the valuation theory which states that an asset is purchased on the basis of expected cash flow in the future. It is recommended for companies to always pay attention to and increase ROAto maintani PBV ratio. Keywords: PBV; ROA; DER; VAIC TM .